Доказать тождество (a+2)³-25(a+2)=(a+2)(a+7)(a-3)

Доказать тождество (a+2)³-25(a+2)=(a+2)(a+7)(a-3)
Гость
Ответ(ы) на вопрос:
Гость
(a+2)³-25(a+2)=(a+2)(a+7)(a-3) (а+2)³*25(а+2)=((а+2)²-25)(а+2)=(а²+4а+4-25)(а+2)=(а²+7а-3а-21)(а+2)=(а(а+7)-3(а+7))(а+2)=(а+2)(а+7)(а-3).
Гость
[latex](a+2)^3-25(a+2)=(a+2)(a+7)(a-3) \\ (a+2)((a+2)^2-25)=(a+2)(a+7)(a-3) \\ (a+2)((a+2)^2-5^2)=(a+2)(a+7)(a-3) \\ (a+2)(a+2-5)(a+2+5)=(a+2)(a+7)(a-3) \\ (a+2)(a-3)(a+7)=(a+2)(a+7)(a-3)[/latex] что и требовалось доказать
Не нашли ответ?
Ответить на вопрос
Похожие вопросы